Capital structure revisited. Do crisis and competition matter in a Keiretsu corporate structure?. (9th July 2020) - Danso, Albert; Fosu, Samuel; Owusu‐Agyei, Samuel; Ntim, Collins G.; Adegbite, Emmanuel
Abstract: We investigate firm‐level determinants of capital structure using a large sample of 4, 284 Japanese firms over a 19‐year period (i.e., over 61, 000 firm‐year observations), a hitherto less examined sample for this purpose. We conduct our analysis and interpret our findings predominantly within the pecking order, the trade‐off and the agency theoretical frameworks. We uncover three new findings. First, our evidence indicates that insights derived from the extant literature on capital structure are cross‐national and are applicable in the context of Japan, despite the unique characteristics of Japanese firms. Second, financial crisis significantly impacts the relationship between leverage and firm‐level determinants, particularly accentuating the effect of asset tangibility and growth. Third, product market competition significantly impacts the observed relationship between firm‐level determinants and leverage. Our results are robust, controlling for the joint effects of competition and crisis.